COMPARISON OF EFFICACY OF TOPICAL BETAMETHASONE LOTION VERSUS TOPICAL KETOCONAZOLE 2% W/V LOTION IN THE TREATMENT OF SEBORRHEIC DERMATITIS (The Research of Medical Science Review, 2025)
Background: Seborrheic dermatitis (SD) has a multifactorial etiology, is a chronic inflammatory dermatosis and is characteristically found in sebum-rich skin areas. Direct comparative evidence of the efficacy of both topical corticosteroids and antifungals in mild to moderate SD is lacking.Objective: Comparison of safety and efficacy of betamethasone dipropionate 0.05% w/v lotion with ketoconazole 2% w/v lotion in mild to moderate seborrheic dermatitis by Seborrheic Dermatitis Area and Severity Index (SDASI) and Visual Analog Scale (VAS) scores.Methods: This 6-month prospective observational cohort study was carried out at Dermatology Department, CMH Abbottabad on 120 clinically diagnosed mild to moderate SD adults (SDASI ≤12), who were enrolled and divided equally into two groups. Group A was treated with betamethasone lotion, whereas Group B was treated with ketoconazole lotion, both applied once a day for 4 weeks. SDASI and VAS scores (pruritus, erythema, and scaling) were documented at baseline and Weeks 1, 2, and 4. Adverse events and recurrence at 6-week follow-up were also noted. Data were analyzed using SPSS v26.Results: 116 patients (58 in each group) completed the study. Mean SDASI decrease at Week 4 was significantly higher in the betamethasone group (5.2 ± 1.7) than in the ketoconazole group (4.3 ± 1.6; p = 0.003). VAS scores for all symptoms improved significantly in both groups with quicker and more relief in the betamethasone group. Median time to ≥50% SDASI decrease was 12 days vs. 16 days (p = 0.009). Both treatments were well tolerated with no difference in adverse effects. Recurrence at 6-week follow-up was slightly higher in the ketoconazole group (22.4% vs. 15.5%; p = 0.32).Conclusion: Topical betamethasone dipropionate 0.05% lotion is more effective in the short-term compared to ketoconazole 2% lotion in the treatment of mild to moderate seborrheic dermatitis, with similar safety. This supports its application in the relief of symptoms quickly, with ketoconazole still being useful for ongoing use. Randomized controlled trials are recommended for long-term outcomes.